Nilai-Nilai Pendidikan Dari Adanya Term Muhkam dan Mutasyabih dalam Tafsir Al-Qur’an - Munir, Zainal Arifin; Anugrah, Adet Tamula (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2021)
This study was conducted to analyze the concept of muhkam and mutasyabih and educational values contained in both terms. The terms muhkam and mutasyabih are rarely understood by teachers as educators in the learning process. These terms are only understood by those who specifically study and analyze the Qur'an in deeply. Because basically the Qur'an is the main reference in Islamic education. So teachers should understand how the concept of muhkam and mutasyabih and understand the values that can be derived from the classification of Qur'anic verses based on these two terms. The research conducted in this paper is a literature approach. The results of this analysis reveal that there are differences of opinion among scholars in analyzing the holy verses of the Qur'an, especially on verses that fall into the mutasyabihat category. From these differences of opinion, the educational values that can be derived from the existence of muhkam and mutasyabih are tolerance values, mujahadah values, tauhid values, and contextual education values.